Pentasaccharides for the treatment of deep vein thrombosis - Brandao, Gustavo M.S. [UNESP]; Junqueira, Daniela R.; Rollo, Hamilton A. [UNESP]; Sobreira, Marcone L. [UNESP] (Wiley, 2017)
Background: Standard treatment of deep vein thrombosis (DVT) is based on antithrombotic therapy, initially with parenteral administration of unfractionated heparin or low molecular weight heparins (LMWH) for five to seven days, then subsequent long-term therapy with oral vitamin K antagonists (e.g. warfarin). Pentasaccharides are novel anticoagulants that may be favourable over standard therapy due to their predictable effect, no need for frequent monitoring or re-dosing, and few known drug interactions. Heparin-induced thrombocytopenia, a harmful effect of heparins, appears to be rare during treatment with pentasaccharides. Objectives: To assess the efficacy and harms of pentasaccharides for the treatment of deep vein thrombosis. Search methods: The Cochrane Vascular Information Specialist (CIS) searched the Specialised Register (22 March 2017) and the Cochrane Central Register of Controlled Trials (CENTRAL) (2017, Issue 2) (searched 22 March 2017). We searched clinical trials databases for details of ongoing or unpublished studies and the reference lists of relevant articles for additional citations. Selection criteria: We included randomised controlled trials in which people 18 years of age or older with a DVT confirmed by standard imaging techniques were allocated to receive a pentasaccharide (fondaparinux, idraparinux, or idrabiotaparinux) for the treatment of DVT in comparison with standard therapy or other treatments. Data collection and analysis: We extracted data characterising the included trials according to the methods, participants, interventions, and outcomes. We assessed risk of bias using Cochrane's 'Risk of bias' tool and employed the GRADE methodology to evaluate the quality of the evidence. The main primary outcome for efficacy was recurrent venous thromboembolism (VTE), and the main primary outcome for harm was major and clinically relevant bleeding. Since our outcomes were dichotomous, we calculated the risk ratio (RR) with a 95% confidence interval (CI). We combined the effects of different comparisons through a meta-analysis using a fixed-effect model. Main results: We included five randomised controlled trials of 6981 participants comparing pentasaccharides with standard therapy or other pentasaccharides. The quality of the evidence varied depending on the outcome and was judged as of moderate to very low quality. We downgraded the quality of the evidence due to risk of bias or imprecision, or both. Two studies evaluated fondaparinux, at doses of 5.0 mg, 7.5 mg, and 10.0 mg, plus vitamin K antagonist in comparison with standard therapy. A meta-analysis of these two studies showed no clear difference in the risk of recurrent VTE (RR 0.80, 95% CI 0.43 to 1.47; 2658 participants); moderate-quality evidence. The frequencies of major bleeding were similar between interventions in the initial period of treatment (approximately five days) (RR 1.15, 95% CI 0.39 to 3.44; 2645 participants) and at three months' follow-up (RR 1.05, 95% CI 0.64 to 1.71; 2645 participants). We judged the quality of the evidence as moderate. One study (757 participants) compared idrabiotaparinux (3.0 mg) with idraparinux (2.5 mg) and demonstrated no clear difference in the risk of recurrent VTE at six months' follow-up (RR 0.72, 95% CI 0.31 to 1.69); low-quality evidence. Major bleeding during the initial treatment period was not reported. Major bleeding at six-month follow-up was less frequent in participants receiving idrabiotaparinux versus participants treated with idraparinux (RR 0.21, 95% CI 0.06 to 0.71); low-quality evidence. The effect of an initial treatment with LMWH followed by three months of idraparinux (10 mg) showed no clear difference from standard therapy for risk of recurrent VTE (RR 1.51, 95% CI 0.26 to 8.90; 263 participants); very low-quality evidence; one study. Major bleeding during the initial treatment period was not reported. The frequency of major and other clinically relevant bleeding at three months' follow-up ranged from 2% to 15% in participants receiving LMWH and increasing doses of idraparinux of 2.5 mg, 5 mg, 7.5 mg, or 10 mg. When dosage groups were combined, there was no clear difference in major plus other clinically relevant bleeding or in major bleeding alone between the idraparinux treatment group and the standard therapy group (RR 1.30, 95% CI 0.70 to 2.40; 659 participants; RR 3.76, 95% CI 0.50 to 28.19; 659 participants, respectively); very low-quality evidence. One study (2904 participants) compared idraparinux (2.5 mg) to standard therapy. There was no clear difference in the risk of recurrent VTE at three months' follow-up (RR 0.98, 95% CI 0.64 to 1.48); low-quality evidence. Major bleeding during the initial treatment period was not reported. Major bleeding at three months of follow-up appeared to be similar in the idraparinux group and the standard therapy group (RR 0.71, 95% CI 0.34 to 1.47); very low-quality evidence. Authors' conclusions: We found moderate-quality evidence that the effects of fondaparinux at doses of 5.0 mg, 7.5 mg, and 10.0 mg plus vitamin K antagonist are similar in terms of recurrent VTE and risk of major bleeding compared with standard treatment for DVT. Low-quality evidence suggests equal efficacy of idraparinux at 2.5 mg and the equimolar dose of 3.0 mg of idrabiotaparinux with regard to recurrent VTE, but a higher frequency of major bleeding was observed in participants treated with idraparinux. We judged evidence on the effectiveness of idraparinux compared with standard therapy, with or without initial treatment with LMWH, and on associated bleeding risk to be low to very low quality, therefore we have very limited confidence in the estimated effects. The observed similar effectiveness in terms of recurrent DVT and harmful effects in terms of bleeding risk with fondaparinux plus vitamin K antagonist compared to standard treatment for DVT suggest that it may be an alternative to conventional anticoagulants for the treatment of DVT in certain circumstances.